Radioactive iodine-refractory differentiated thyroid cancer: unmet needs and future directions. Issue 5 (September 2012) - Pacini, Furio; Ito, Yasuhiro; Luster, Markus; Pitoia, Fabian; Robinson, Bruce; Wirth, Lori
Approximately 90% of thyroid cancers are differentiated (DTCs) and have papillary, follicular or Hürthle cell morphology. Although treatment with surgery and radioactive iodine (I-131; RAI), as appropriate, is associated with significant cure rates and survival benefits, clonal disease progression with development of refractoriness to RAI poses a major therapeutic challenge in about 15% of patients. Traditional chemotherapeutic agents are relatively ineffective and are associated with significant toxicities. Molecular studies have demonstrated that the development and progression of DTC are associated with a series of consistent abnormalities in pathways such as MAPK/ERK and PI3/Akt, which govern cellular growth, proliferation, apoptosis and angiogenesis. Small molecular inhibitors that target these pathogenic pathways, without many of the impairments associated with cytotoxic chemotherapy, have demonstrated efficacy in a variety of malignancies, including renal cell carcinoma, hepatocellular carcinoma, non-small-cell lung cancer and chronic myelogenous leukemia. Several targeted therapeutic agents are in development for the treatment of RAI-refractory DTC. Sorafenib and lenvatinib are being studied in placebo-controlled Phase III trials based on encouraging efficacy results observed in single-arm Phase II studies.